It Takes All Kinds: Sexuality and Gender Differences in Hildegard of Bingen's ‘Book of Compound Medicine’ - Cadden, Joan (1984)
Hildegard of Bingen, a twelfth-century religious visionary and head of a convent, wrote extensively and frankly about sex difference and sexual behavior in her general treatise in medicine. Gender differences, sexuality, and reproduction were subjects by no means proscribed in twelfth-century Europe. Whether we look at canon law, which prohibited various forms of sexual behavior, or vernacular literature, which sometimes celebrated them, we find no unwillingness to acknowledge the existence of human sexuality. Yet aside from tracts addressed specifically to gynecological and reproductive disorders, most works of twelfth-century naturalists and medical authors treat such matters only cursorily. Hildegard was an exception, and her treatment of sexuality was both wide-ranging and undogmatic. It is the purpose of this study to explicate Hildegard's ideas on these subjects — especially on the sexual characteristics and reproductive contributions of women and men — and to evaluate the significance of the content and extent of her exposition.